2010
DOI: 10.1097/ede.0b013e3181d61dbc
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Socially Desirable Responses in Epidemiologic Surveys

Abstract: Given the considerable discrepancy between the results obtained by direct questioning and by using the randomized-response technique, we propose that this technique be considered for use in epidemiologic studies of sensitive behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…In the DQ condition, the proportion of respondents answering Btrue^to the direct question provides a direct prevalence estimate. Following the procedure detailed in Moshagen, Hilbig, and Musch (2011), , , Moshagen et al (2010), Ostapczuk, Moshagen, et al (2009), ), Ostapczuk, Musch, et al (2009, however, we formulated multinomial processing tree models (MPT; Batchelder, 1998;Batchelder & Riefer, 1999) for all three questioning techniques. This approach offers more flexibility in parameter estimation and convenient statistical tests of parameter restrictions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the DQ condition, the proportion of respondents answering Btrue^to the direct question provides a direct prevalence estimate. Following the procedure detailed in Moshagen, Hilbig, and Musch (2011), , , Moshagen et al (2010), Ostapczuk, Moshagen, et al (2009), ), Ostapczuk, Musch, et al (2009, however, we formulated multinomial processing tree models (MPT; Batchelder, 1998;Batchelder & Riefer, 1999) for all three questioning techniques. This approach offers more flexibility in parameter estimation and convenient statistical tests of parameter restrictions .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to considering carriers of the sensitive attribute who answer honestly (π) and noncarriers who answer honestly (β), it considers a third class of respondents, namely cheaters (γ) who respond BNo^regardless of the outcome of the randomization procedure. Various studies have shown that the CDM provides higher and thus potentially more valid prevalence estimates of sensitive attributes than a direct question (e.g., Moshagen et al, 2010;Ostapczuk, Moshagen, et al, 2009;Ostapczuk, Musch, et al, 2009;Ostapczuk, Musch, & Moshagen, 2011;Pitsch, Emrich, & Klein, 2007). However, the CDM does not make any assumptions about the real status of cheaters; they may be either lying carriers or noncarriers who wish to avoid suspicion.…”
Section: The Randomized Response Technique (Rrt)mentioning
confidence: 99%
“…Although findings to date are inconclusive regarding the direction of this effect, females generally find lying less acceptable then males [30][32]. A recent study investigating dental hygiene found that admission of insufficient dental hygiene doubled for females when a less intrusive method was used, but increased only by 46% among males [33], indicating not only gender but interaction between gender- and method effect. Therefore, regarding potential gender differences, we hypothesise that…”
Section: Introductionmentioning
confidence: 98%
“…In other words, these methods estimate the proportion of carriers of the sensitive attribute not for the total population of interest, but only for the latent subpopulation of respondents who adhere to the instructions. Unfortunately, the rate of nonadherence may be often substantial, with estimates ranging from 5% to 50% (e.g., Moshagen, Hilbig, & Musch, 2011;Moshagen, Musch, Ostapczuk, & Zhao, 2010;Ostapczuk, Musch, & Moshagen, 2009b;in press).…”
mentioning
confidence: 99%